Antidiabetic Effectiveness Test of Ethanol Extract of Brown Leaves (Theobroma Cacao L.) Against Mice (Mus Musculus) - Gunawan, Muhammad; Safriana; Tanjung, Siti Aisyah; Andilala (International Journal of Public Health Excellence (IJPHE), 2024)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both. DM sufferers are increasing from year to year, accompanied by increasing costs of therapy, therefore, as an alternative to controlling blood glucose levels, use natural ingredients such as cocoa leaves. The aim of this research was to determine the effectiveness of ethanol extract of cocoa leaves (Theobroma cacao L.) in reducing blood glucose levels in mice that had been induced by Aloxan. The research method used was experimental research. The research stages were sample collection, sample identification, making simpilicia, examining the characteristics of simpilicia, making extracts using maceration using 96% ethanol solvent, and testing the antidiabetic effect of EEDC in mice induced by alloxan at a dose of 175 mg/kg. bb intraperitoneally. Diabetic mice were divided into 5 groups, each group consisting of 5 mice that were given the test material 50 mg/KgBB of ethanol extract of brown leaves; 100 mg/KgBB; and 200 mg/KgBB, Metformin 65 mg/KgBB, and CMC 0.5%. Next, blood glucose levels were measured on days 3, 6, 9, 12, and 15, the percentage reduction in blood glucose levels was calculated, then the data was analyzed using the One-Way ANOVA method and Duncan's test, to see real differences between treatments. The research results showed that simplicia, the ethanol extract of brown leaves contains flavonoids, alkaloids, tannins, steroids/triterpenoids, saponins and glycosides. Cocoa leaf ethanol extract has effectiveness in lowering glucose levels, at the 5th and 6th hours it shows good effectiveness at a dose of 200 mg/KgBW of (72.16 ± 0.1.51)% and (82.80 ± 0.73 )%, not significantly different from metfromin 65 mg/KgBB of (74.45 ± 1.51)% and (83.29 ± 1.01).